Good Capital and Better World Books. (A), A better world for investing - Jones, Jamie, (SAGE knowledge. Cases., 2016)
The purpose of this case is to introduce the topic of socially responsible investing from both the investor and investee perspectives. The students will walk away with an understanding of how to evaluate a portfolio company on a social/environmental mission and on traditional financial criteria, as well as understanding what considerations should be top of mind for a social venture considering accepting an equity investment.